2021
DOI: 10.1158/1078-0432.ccr-20-2415
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning Algorithms to Predict Immunotherapy Response in Patients with Advanced Melanoma

Abstract: Purpose: Several biomarkers of response to immune checkpoint inhibitors (ICI) show potential but are not yet scalable to the clinic. We developed a pipeline that integrates deep learning on histology specimens with clinical data to predict ICI response in advanced melanoma. Experimental Design: We used a training cohort from New York University (New York, NY) and a validation cohort from Vanderbilt University (Nashville, TN).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 37 publications
0
69
2
2
Order By: Relevance
“…Johannet and colleagues reported a more advanced AI approach using CNNs trained and tested on treatment-naïve histopathology slides together with patients' clinical characteristics to predict responses to checkpoint immunotherapy in patients with advanced melanoma (AUC, 0.80; ref. 96).…”
Section: Patient Prognosis and Response To Therapymentioning
confidence: 99%
“…Johannet and colleagues reported a more advanced AI approach using CNNs trained and tested on treatment-naïve histopathology slides together with patients' clinical characteristics to predict responses to checkpoint immunotherapy in patients with advanced melanoma (AUC, 0.80; ref. 96).…”
Section: Patient Prognosis and Response To Therapymentioning
confidence: 99%
“…These results were then combined through a multivariable logistic regression with clinical characteristics such as age, gender, histologic subtypes, etc. The classi er accurately strati ed patients into high versus low risk for disease progression with an AUC = 0.80 (32). Lastly, in another work regarding IO prediction in bladder cancer CT-scans were used to develop a ML model according to RECIST methodology and the ROI were processed to extract radiomic features.…”
Section: Discussionmentioning
confidence: 99%
“…Johannet el al . developed a pipeline that integrates DL on histology specimens with clinical data to predict immunotherapy response in advanced melanoma [72]. The results showed that the classifier accurately stratified patients into responders and non‐responders with an AUC of 0.80.…”
Section: Patient Prognosis Response To Therapy and Precision Medicinementioning
confidence: 99%